The Politicized Motivations of Volunteers in the Refugee Crisis: Intergroup Helping as the Means to Achieve Social Change - Anna Kende; Nóra Anna Lantos; Anna Belinszky; Sára Csaba; Zsófia Anna Lukács (Journal of Social and Political Psychology, 2017)
The refugee crisis in the summer of 2015 mobilized thousands of volunteers in Hungary to help refugees on their journey through Europe despite the government’s hostile stance. We conducted a survey (N = 1459) among people who were active in supporting refugees and providing services to them to test the hypothesis of whether volunteers in the context of this humanitarian crisis had social change motivations similar to those engaged in direct political activism. Hierarchical regression analysis and mediation analysis revealed the importance of opinion-based identity and moral convictions as predictors of volunteerism, while efficacy beliefs and anger only predicted political activism. Our findings suggest that volunteers engaged in helping refugees based on motivations previously described as drivers of mobilization for political activism, but chose volunteerism to alleviate the problems embedded in the intergroup situation. Although the context of the refugee crisis in Hungary may have been somewhat unique, these findings have implications for other asymmetrical politicized intergroup relations in which advantaged group members can choose to offer humanitarian aid, engage in political actions to change the situation, or do both.